The three-dimensional structure of crust and upper mantle in Mare Orientale from gravity inversion - Yu, Hangtao; Wen, Mingming; Xu, Chuang; He, Qingyin (Frontiers in Earth Science, 2025)
As one of the representative multi-ring basins on the Moon, the internal structure of Mare Orientale is crucial for exploring the formation mechanism of multi-ring basins. Due to the sparsity of moonquake data, at present, only gravity data can be more effectively applied to study the internal structure of Mare Orientale. Therefore, based on the GRGM1200A model from Gravity Recovery and Interior Laboratory, we inverted the internal density structure of Mare Orientale from the perspective of signal separation. In addition, based on the gravity anomalies after deducting the influence of the crust, we calculated the depth of its crust-mantle interface. The results of the study show that there is a wide-ranging, high-density body beneath Mare Orientale. Its morphology is similar to that of a prism, with a depth ranging from 32.4 to 64.0 km. The upper tip is located roughly 98°W longitude and 18°S latitude, and the lower tip roughly 94°W longitude and 22°S latitude. Within the internal depression, the crust-mantle interface in Mare Orientale is clearly uplifted with a shallowest depth of 1.47 km. In the basin centre, there is an uplifted rebound of the crust-mantle interface. Based on our results, we suggested that the multi-ring structure of Mare Orientale was formed primarily by a large, tilted meteorite impact, which left meteorite residues in the upper mantle of Mare Orientale and caused a dramatic uplift of the crust-mantle interface within the basin.